Acceptance of e-Learning Applications at Indonesian Universities Using the Extended Technology Acceptance Model - Mohammad Al Hafidz (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2022)
The emergence of the COVID-19 pandemic in Indonesia has an impact on the implementation of distance learning (e-learning) in Indonesian universities. However, the adoption of LMS technology as an e-learning medium in Indonesia has many obstacles, ranging from internet access, content, to users. This study was made to determine the perception of acceptance of the use of e-learning applications using the Extended Technology Acceptance Model (TAM). This research can be used as a strategy for implementing e-learning in higher education so that it can be accepted by students and then students really intend to use it. The respondents of this study were UHW Perbanas students with a sampling technique of 100 students spread over almost all study programs. The research data is primary data with the technique of collecting it using a questionnaire. Data analysis techniques with SmartPLS application tools. The results of research processing showed that all instruments were declared valid and reliable. The results of the hypothesis test indicate that the perceived usefulness of e-learning applications is significantly influenced positively by the characteristics of the lecturers and the quality of the content. Students' perception of ease of using e-learning applications is significantly influenced positively by content design and accessibility of e-learning.